1997
DOI: 10.1097/00005537-199711000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Adhesion Molecules in Nonallergic Chronic Sinusitis

Abstract: Endothelial and epithelial adhesion molecules are important in the recruitment of leukocytes to inflammatory sites. To determine the relationship between recruited leukocytes and adhesion molecules in the paranasal sinus mucosa of nonallergic chronic sinusitis, we surgically obtained mucosa from 16 patients and identified the expression of intercellular adhesion molecules (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1), E-selectin, and P-selectin by immunohistochemistry. Neutrophils were significantly dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Administration of EM inhibited accumulation of neutrophils in the middle ear after LPS stimulation. It is well known that adhesion molecules are involved in the infiltration of leukocytes to the foci of inflammation, and that the modulation of adhesion molecules affects the migration of leukocytes (6,7). Leukocytes migrate into the inflammatory tissues through the vascular endothelia in two stages: the first stage is called rolling, where L-selectin is involved, and the second stage is called firm adhesion, where the i 2 -integrins Mac-1 and LFA-1 are involved.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of EM inhibited accumulation of neutrophils in the middle ear after LPS stimulation. It is well known that adhesion molecules are involved in the infiltration of leukocytes to the foci of inflammation, and that the modulation of adhesion molecules affects the migration of leukocytes (6,7). Leukocytes migrate into the inflammatory tissues through the vascular endothelia in two stages: the first stage is called rolling, where L-selectin is involved, and the second stage is called firm adhesion, where the i 2 -integrins Mac-1 and LFA-1 are involved.…”
Section: Discussionmentioning
confidence: 99%
“…The recruitment and migration of inflammatory cells at sites of mucosal inflammation involve a variety of adhesion molecules [1]. Nonallergic chronic sinusitis is characterized by purulent paranasal sinus effusion and persistent nasal discharge with numerous emigrated neutrophils [2, 3, 4, 5, 6, 7, 8, 9], in additon to the accumulation of eosinophils in the tissue [5, 10, 11, 12, 13]. Tokushiga et al [14]proposed that IL–1β induces the expression of both intercellular adhesion molecule–1 (ICAM–1) and E–selectin on ECs, presumably leading to neutrophil infiltration.…”
Section: Introductionmentioning
confidence: 99%
“…We recently demonstrated that IL–8 generated by emigrated neutrophils and mucosal epithelia plays a pivotal role in the selective neutrophil migration into the sinus effusion [6]. More recently, we revealed that ICAM–1 expression in mucosal microvascular EC was correlated to neutrophil infiltration into the sinus mucosa and contributed to the establishment of the inflammatory cell distribution in patients with nonallergic chronic sinusitis [7]. On the other hand, the driving force for eosinophil accumulation in the sinus mucosa was associated with endothelial vascular cell adhesion molecule–1 (VCAM–1) upregulation induced by TNF–α [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, under pathophysiological conditions, other cell types are found to express P-selectin. Notably, it has been reported that epithelial cells from breast carcinomas, 16 from paranasal chronic sinusitis mucosa, 17 and from glomerulonephritis biopsies 18 express P-selectin. This property has been exploited in this study to develop a model system to assess the role of vWF in the sorting of P-selectin and the biogenesis of WPB-like organelles.…”
mentioning
confidence: 99%